Employee ownership as a form of economic democracy - Erdal, David (Teorija in praksa, 2012)
This paper provides a critique of the conventionally dominant model that has driven the world economy to the brink of collapse, a model that predicts failure for employee-owned and democratically structured firms. The paper contrasts these predictions with the success achieved by employee-owned companies structured democratically. Two case studies, the John Lewis Partnership in the UK and Mondragon in Spain show that democratically structured enterprises can succeed extremely well. Evidence is reported suggesting that people thrive with democratic ownership.
Keywords: Economic democracy; Ekonomska demokracija; Enterprises; Podjetja; Zaposleni; Employees; Lastništvo; Ownership; economics; ekonomija